Polysomnography applied to patients with tinnitus : a review - Teixeira, Liane Sousa (2018)
Introduction Tinnitus has been defined as an “auditory phantom perception,” meaning that tinnitus results from an abnormal activity within the nervous system, in the absence of any internal or external acoustic stimulation. About 10 to 15% of the adult population is affected by tinnitus, and a relevant percentage of tinnitus sufferers experience symptoms severe enough to significantly affect quality of life, including sleep disturbances, work impairment, and, in some cases, psychiatric distress. The selfrated complaints about tinnitus focus on emotional distress, auditory perceptual difficulties, and sleep disturbances. Objectives To evaluate the works that show sleep disorders in patients with tinnitus, and sleep disorders assessed by polysomnography. Data Synthesis We found four studies with polysomnography to assess sleep disorders in patients with tinnitus. The first study evaluated 80 patients who were military personnel without major psychiatric disturbances, and their tinnitus was associated with noise-induced permanent hearing. The second study was a prospective, case-control, nonrandomized study of 18 patients affected by chronic tinnituswho were compared with a homogeneous control group consisting of 15 healthy subjects. The last work evaluated questionnaires mailed to patients before their initial appointment at the Oregon Health Sciences University Tinnitus Clinic between 1994 and 1997. These questionnaires requested information pertaining to insomnia, tinnitus severity, and loudness. Follow-up questionnaires were mailed to 350 patients 1 to 4 years (mean 5 ± 2.3 years) after their initial appointment at the clinic. Conclusion There are few studies with polysomnography for the evaluation of patients with sleep disorders caused by tinnitus. This shows the need for more studies on this subject.